Formulation and Optimization of Fast Dissolving Thin Strips of Desvenlafaxine HCl by Using Quality by Design (QbD) Approach - Kumar, Ganesh; Bhatt, Meenakshi; Dhyani, Archana (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: The present work was aimed to formulate and optimize fast dissolving thin strips of Desvenlafaxine Hydrochloride using QbD. Materials and Methods: The solvent casting method was used to formulate fast dissolving thin strips. The drug (Desvenlafaxine HCl), polymer (pullulan), super disintegrant (Croscarmellose sodium), plasticizer (Poly Ethylene Glycol- (PEG-400), saliva stimulating agent (citric acid), sweetening agent (mannitol and aspartame) and water (solvent) were used in the preparation of the strips. The study involved a 3-level factorial design in which the effect of Pullulan Polymer (A), Croscarmellose Sodium (B) and Poly Ethylene Glycol (C) on 3 response variables disintegration Time (X), percent swelling index (Y) and percent Dissolution Efficiency (DE%15) were analyzed. Results: From the studies, it was found that F12 formulation (containing 30% pullulan, 5% CCS and 7.5% PEG) was the optimized formulation that showed improved important strip characteristics including disintegration time, swelling index and dissolution efficiency after 15 min.
Keywords: Crospovidone; Disintegration time; Dissolution efficiency; Dysphagia; Fast dissolving; strips; Microcystalline Cellulose; Quality by Design